1985
DOI: 10.1080/07055900.1985.9649234
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hudson Bay on the energy balance in the Hudson Bay Lowlands and the potential for climatic modification

Abstract: Three sites were instrumented to measure all components of the energy balance. The sites were located in the Churchill, Manitoba region and comprised a Sea Site on a sand spit 1 km seaward from the mainland, a Nearcoast Site 2 km inland from the coast and an Inland Site 65 km inland. Measurements were made continuously over a 90-day period from 19 May to 16 August 1984. This period encompassed the bulk of the growing season.The measurements were stratified into onshore and offshore wind directions and were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 6 publications
4
18
1
Order By: Relevance
“…The results from the third objective are presented in a companion paper (Weick and Rouse, 1991). Previous studies have indicated that advection from a cold sea has a strong impact on the surface energy balance in the Hudson and James Bay Lowlands during the growing season (Rouse, 1984a;Rouse and Bello, 1985;Rouse et al, 1987;Lafleur and Rouse, 1988). These studies have indicated, in general, that onshore marine air flow serves to suppress the latent heat flux and enhance the sensible heat flux, the two largest fluxes in the energy balance at the surface.…”
Section: Introductionmentioning
confidence: 93%
“…The results from the third objective are presented in a companion paper (Weick and Rouse, 1991). Previous studies have indicated that advection from a cold sea has a strong impact on the surface energy balance in the Hudson and James Bay Lowlands during the growing season (Rouse, 1984a;Rouse and Bello, 1985;Rouse et al, 1987;Lafleur and Rouse, 1988). These studies have indicated, in general, that onshore marine air flow serves to suppress the latent heat flux and enhance the sensible heat flux, the two largest fluxes in the energy balance at the surface.…”
Section: Introductionmentioning
confidence: 93%
“…This arises because cold temperatures correlate with the mesoscale advection of moist air that originates over Hudson Bay, whereas warm temperatures are associated with air of lower relative humidity, which is advected from the interior of the continent (Rouse and Bello, 1985;Rouse et al, 1987).…”
Section: Seasonal Precipitation Temperature and Vapour Pressurementioning
confidence: 99%
“…The role of advection in a marine environment was considered by Rouse and Bello (1985)) and Rouse et al (1987). They found that cold onshore winds enhance the sensible heat flux over the latent flux.…”
Section: Introductionmentioning
confidence: 99%